2010
DOI: 10.1177/0165025409354933
|View full text |Cite
|
Sign up to set email alerts
|

Children’s perceptions of maternal hostility as a mediator of the link between discipline and children’s adjustment in four countries

Abstract: Using data from 195 dyads of mothers and children (age range = 8-12 years; M = 10.63) in four countries (China, India, the Philippines, and Thailand), this study examined children's perceptions of maternal hostility as a mediator of the links between physical discipline and harsh verbal discipline and children's adjustment. Both physical discipline and harsh verbal discipline had direct effects on mothers' reports of children's anxiety and aggression; three of these four links were mediated by children's perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…The salient relationship may be because children expect their mother to be protective and warm. Hence, maternal physical abuse may be regarded as rejection and denial, and hence, increases children’s vulnerability to behavioral problems (Lansford et al, 2010). However, it is inconsistent with the finding in Wang et al (2016) that, in a Chinese sample, maternal physical abuse was not significantly related to child anxiety after adjusting for maternal and paternal psychological aggression and physical punishment, paternal physical abuse, and other covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salient relationship may be because children expect their mother to be protective and warm. Hence, maternal physical abuse may be regarded as rejection and denial, and hence, increases children’s vulnerability to behavioral problems (Lansford et al, 2010). However, it is inconsistent with the finding in Wang et al (2016) that, in a Chinese sample, maternal physical abuse was not significantly related to child anxiety after adjusting for maternal and paternal psychological aggression and physical punishment, paternal physical abuse, and other covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, child gender was not taken into consideration in examining the effect of maternal and paternal physical abuse, considering the small sample size of children who were abused solely by one parent. Several studies suggest that the occurrence and effect of child abuse are functions of both parents and child gender (Braza et al, 2015; Cui et al, 2016; Hoeve et al, 2011; Lansford et al, 2010). Future studies are needed to investigate both the interaction between parents and child gender in the relationship between child abuse and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Lansford, Alampay, et al, 2010; Raudino et al, 2013), Italian students more often rated their mothers and fathers as less positive and secure, but less often the perpetrators of emotionally abusive behaviour toward them, as well as physically abusive behaviour both towards them directly and towards others in their family. Indeed, prior studies suggested that Canadian parents tend to be more diplomatic than Italians, who tend to enforce stricter rules on their children, sometimes also using corporal punishment, which remain more acceptable within the Italian culture as compared to North American families (Lansford, Alampay, et al, 2010; Lansford, Malone et al, 2010). In contrast to this, some studies (Hsu & Lavelli, 2005; Raudino et al, 2013) considered Italian mothers to be particularly warm, emotional and social caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The harsh verbal parenting construct included Shame and Verbal Discipline subscales that were adapted from the Discipline Questionnaire (Lansford et al, 2010). These combined scales have been used previously in a measure of maternal harsh negativity (Deater-Deckard et al, 2012).…”
Section: Methodsmentioning
confidence: 99%